2022
DOI: 10.1177/21582440221089956
|View full text |Cite
|
Sign up to set email alerts
|

Non-Financial Enterprise Financialization, Product Market Competition, and Total Factor Productivity of Enterprises

Abstract: At present, two big challenges have struck China’s economic development: economic containment “from the real to the virtual” and accomplishment in the goal of high-quality economic development. Taking China’s A-share public manufacturing enterprises from 2007 to 2020 as samples, this paper empirically analyzes the relationships among product market competition, non-financial enterprise financialization, and total factor productivity of enterprises. It is found that non-financial enterprise financialization sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…For example [ 19 ], empirically showed that, the higher the proportion of profits obtained through financial channels is, the lower the economic value added (EVA) of entity enterprises will be. In terms of enterprise efficiency, [ 20 , 21 ]; and [ 22 ] all showed that the financialization of entity enterprises has an impact on production efficiency. However, there is controversy regarding the specific impact direction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example [ 19 ], empirically showed that, the higher the proportion of profits obtained through financial channels is, the lower the economic value added (EVA) of entity enterprises will be. In terms of enterprise efficiency, [ 20 , 21 ]; and [ 22 ] all showed that the financialization of entity enterprises has an impact on production efficiency. However, there is controversy regarding the specific impact direction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, the economic consequences of digital transformation mainly include "promotion view" and "challenge view." (1) e positive effects of digital transformation. A large number of studies have shown that through the deep integration of digital technology and enterprise strategy, digital transformation will lead to systematic changes in enterprise strategic logic, management mode, competition mode, business ecology, etc.…”
Section: Research On the Economic Consequences Of Digitalmentioning
confidence: 99%
“…(1) e regulating effect of property right nature: column (1) shows the regulating effect of property right nature. It can be found that the regression coefficient of the interaction term between MSQ and SOE is −39.823, which is significant at 1% level, indicating that the property right will make the relationship curve between MS and DITL become steeper.…”
Section: Analysis Of the Moderation Effectmentioning
confidence: 99%
See 2 more Smart Citations